2018
DOI: 10.21873/invivo.11428
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sepsis-induced Immunosuppression and Serum Toll-like Receptor 9 Level

Abstract: Background/Aim: Our aim was to determine serum TLR-9 levels in sepsis and evaluate the relationship between sepsis and serum TLR-9 levels. Materials and Methods: The study group consisted of 80 consecutive patients with sepsis and 100 healthy individuals. The demographic characteristics, co-morbidities and hemodynamic data of all patients were recorded. Results: TLR-9 serum levels in sepsis were statistically significantly lower compared to the control group. It was also seen that when the lactate level was >5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Macrophage-derived exosomes can participate in innate immune response-induced inflammation through synergistic action with toll-like receptors (TLR) [ 13 ]. TLR are regarded as an integral part of the innate immune system [ 14 ], among which TLR9 can recognize microbial DNA [ 15 ]. Moreover, it has been found that macrophage-derived exosomes can recognize long-chain fatty acids, activate the downstream ERK signaling pathway, and promote the secretion of inflammatory factors [ 16 ] and proinflammatory cytokines such as TNF- α and L-1 β , thus inducing the systemic inflammatory cascade response and causing myocardial injury, apoptosis, and cardiac dysfunction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage-derived exosomes can participate in innate immune response-induced inflammation through synergistic action with toll-like receptors (TLR) [ 13 ]. TLR are regarded as an integral part of the innate immune system [ 14 ], among which TLR9 can recognize microbial DNA [ 15 ]. Moreover, it has been found that macrophage-derived exosomes can recognize long-chain fatty acids, activate the downstream ERK signaling pathway, and promote the secretion of inflammatory factors [ 16 ] and proinflammatory cytokines such as TNF- α and L-1 β , thus inducing the systemic inflammatory cascade response and causing myocardial injury, apoptosis, and cardiac dysfunction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive immune responses are detrimental to the host and negative feedback regulation, and PI3K plays as a primary endogenous suppressor for TLR-induced inflammatory signals in macrophages, which is crucial for the maintenance of immune system as well as cellular structure integrity [18][19][20]. Previously, much studies were focused on the inflammatory responses and TLR9 signals, whereas the relationship between the PI3K signal-induced exosome secretion and TLR9 activation remains unclear and ambiguous [15,21]. Therefore, this study was carried on to elaborate on these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, TLR9 (-1486 T > C) and TLR-9 (C > T) gene polymorphisms do not show any correlation with sepsis [67] . The serum TLR9 levels are low in sepsis patients but their circulating levels increases at later immunosuppressive stage of sepsis, including septic shock in patients with a higher (greater than 5 mmol/l) lactate level [68] . This indicates that the profound immune cell death may have caused the increase in the circulating TLR9 (recognizes bacterial and viral DNA).…”
Section: Tlrs In Sepsismentioning
confidence: 98%
“…RIG1 mRNA was also upregulated in human sepsis patients but not the protein expression [ 101 ]. In sum, all that can be said in general about innate activation in sepsis is that TLR2, TLR4, TLR5, TLR7 and NLRP3 [ 102 ] can be, but are not necessarily, activated, while TLR9 may or may not be downregulated [ 103 , 104 , 105 ]. The same generalizations can be made about murine polymicrobial sepsis models [ 91 , 106 , 107 , 108 ], suggesting that sepsis is not a single, definable disease [ 97 ].…”
Section: Innate Immune System Receptor Activation In Cytokine Stormentioning
confidence: 99%